(untitled) (Medico Legal Update, 2019)
Background and Objective: Vitamin D receptor is considered genetic variants that related with vitamin D status. Our study was recorded polymorphism in vitamin D receptor (VDR) FokI in beta thalassemia children. In this study has been shown polymorphism VDR FokI dominant (FF) ,hybrid(Ff).VDR is includes a beginning codon polymorphism (BCP) that consist of three codon above the course of a second beginning site (ATG).The BCP can be located by the restriction enzyme Fok I,which allele(f)references first of the restriction site ATG is presents, whereas the allele(F) references its missing . Materials and Methods: In this study vitamin D3 levels were evaluated by Enzyme Linked Immunosorbent Assay(Elisa).FokI gene polymorphism were analyzed by using polymerase chain reaction- restriction fragment length polymorphism assay (PCR-RFLP) were estimated in 50 participants children beta thalassemia were distributed to 25 male and 25 female. Results: Patients had significant decrease vitamin D and serum calcium p=0.084 and p=0.751 respectively, alkaline phosphate was recorded p=0.665, potassium= 0.278 and total protein p=0.521. in the male study 84% had VD insufficiency and 16% deficiency ,female study 96%had VD insufficiency and 4% deficiency . Conclusion: Vitamin D3 was higher in female more than male and recorded in age category 9-12 years old .VDR FokI gene polymorphism effect VD status ,genotype FF,Ff appeared in our study and absence genotype ff.